Elevating Problem-Solving Prowess: The Impact of ICT-Assisted ReCODE Learning Model on Class VIII Students' Problem-Solving Skills at SMPN 18 Makassar - Sitti Saenab; St Asriani; Nurhayani H Muhiddin; Andi Rahmat Saleh (Postgraduate, University of Mataram, 2024)
Problem-solving skills are one of the 21st-century skills that are important to improve, especially in the field of science. However, some studies show that students' problem-solving skills are still low. This study aims to determine the effect of the ICT-assisted Reading, Connecting, Observing, Discussing, Evaluating (ReCODE) learning model on students' problem-solving skills. This research is a quasi-experimental research with Pretest-Posttest Nonequivalent Control Group Design research design. The study population was all students of class VIII SMPN 18 Makassar. Sampling using a purposive sampling technique which consisted of experimental class and control class. The instrument used was an essay test instrument with data collection methods using pre-test and post-test results. Data were analyzed using descriptive and inferential statistical analysis. The results of the analysis were obtained tcount = 2.4 > ttable = 1.67 which means H0 is rejected and H1 is accepted. Based on these results, it can be concluded that the ReCODE Learning model assisted by ICT affects the problem-solving skills of class VIII students of SMPN 18 Makassar.